2002
DOI: 10.1034/j.1600-0560.2002.290311.x
|View full text |Cite
|
Sign up to set email alerts
|

Fibroepithelioma‐like changes occurring in perianal Paget's disease with rectal mucinous carcinoma: case report and review of 49 cases of extramammary Paget's disease

Abstract: Anogenital PD was more frequently associated with epidermal hyperplasia than axillary PD. Fibroepitheliomatous hyperplasia may be induced by the altered stroma associated with PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Two previous studies have shown that EMPD may be associated with a significant epidermal hyperplasia. 23,24 Immunohistochemical studies will be helpful by highlighting the expression in the tumor cells of antikeratin antibodies and other epithelial markers (carcinoembryonic antigen, epithelial membrane antigen, mucoproteins, etc) but not melanocytic markers (Mart-1 or HMB-45 antigen). However, due to some unexpected findings (such as S100 protein expression by some breast carcinoma cells or the apparent overexpression of Mart-1 by dysplastic keratinocytes in pigmented actinic keratoses), 25 the use of antibody panels are recommended to clearly determining the pattern of differentiation (that is, epithelial or melanocytic) of the tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Two previous studies have shown that EMPD may be associated with a significant epidermal hyperplasia. 23,24 Immunohistochemical studies will be helpful by highlighting the expression in the tumor cells of antikeratin antibodies and other epithelial markers (carcinoembryonic antigen, epithelial membrane antigen, mucoproteins, etc) but not melanocytic markers (Mart-1 or HMB-45 antigen). However, due to some unexpected findings (such as S100 protein expression by some breast carcinoma cells or the apparent overexpression of Mart-1 by dysplastic keratinocytes in pigmented actinic keratoses), 25 the use of antibody panels are recommended to clearly determining the pattern of differentiation (that is, epithelial or melanocytic) of the tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…4), aldehyde‐fuchsin and toluidin blue. The epidermis is often hyperplastic, sometimes showing fibroepithelioma‐like changes 70 . Suprabasal intra‐epidermal acantholytic clefts may be found, mimicking Darier's disease or familial pemphigus.…”
Section: Extramammary Paget's Diseasementioning
confidence: 99%
“…However, although its significance remains unknown, the simultaneous occurrence of EMPD and other epidermal proliferative diseases has been reported [2, 3, 4, 5, 6, 7, 8]. Brainard and Hart [6]described the reactive proliferating epidermal lesions in anogenital EMPD and stressed the fact that EMPD might mimic condyloma acuminatum (CA), a human-papillomavirus (HPV)-associated epidermal neoplasm affecting the anogenital region [9].…”
Section: Introductionmentioning
confidence: 99%